Parasocial Relationship between Parents Viewers with Korean Drama Actors - Aurelia Angelica Ng; Jandy Luik; Chory Angela Wijayanti (Communication Science Department - Petra Christian University, 2023)
Hallyu or Korean wave has been rapidly growing on the last few decades. Hallyu has brought South Korea’s cultures including Korean dramas worldwide, including Indonesia. The rise of technology and new media has also given more space for content distribution and access for media actors and audiences. Hence, Korean drama has a high popularity in Indonesia, with audiences from various kinds of demographic backgrounds, including parents. One of the reasons of the high interest towards Korean drama is due to the interesting actors. The high interest towards Korean drama actors are often related to the concept of parasocial relationship, which is a one-sided relationship between audiences and media persona. This research aims to determine the parasocial relationship that exists between parents viewers and Korean drama actors. The research method that is used in this study is qualitative case study with semi-structured interview as the data gathering technique. The result of this study shows that the parasocial relationship that exists belongs in the entertainment-social value level due to the informants who find the personas to be entertaining, attractive, and as references for their daily decisions. The parasocial relationship is also found as a form of media effect especially in terms of media cultivation and third person effect.